Verb and sentence processing with TMS: A systematic review and meta-analysis. (May 2023) - Ntemou, Effrosyni; Svaldi, Cheyenne; Jonkers, Roel; Picht, Thomas; Rofes, Adrià
Abstract: Transcranial magnetic stimulation (TMS) has provided relevant evidence regarding the neural correlates of language. The aim of the present study is to summarize and assess previous findings regarding linguistic levels (i.e., semantic and morpho-syntactic) and brain structures utilized during verb and sentence processing. To do that, we systematically reviewed TMS research on verb and sentence processing in healthy speakers, and meta-analyzed TMS-induced effects according to the region of stimulation and experimental manipulation. Findings from 45 articles show that approximately half of the reviewed work focuses on the embodiment of action verbs. The majority of studies (60%) target only one cortical region in relation to a specific linguistic process. Frontal areas are most frequently stimulated in connection to morphosyntactic processes and action verb semantics, and temporoparietal regions in relation to integration of sentential meaning and thematic role assignment. A meta-analysis of 72 effect sizes of the reviewed papers indicates that TMS has a small overall effect size, but effect sizes for anterior compared to posterior regions do not differ for semantic or morphosyntactic contrasts. Our findings stress the need to increase the number of targeted areas, while using the same linguistic contrasts in order to disentangle the contributions of different cortical regions to distinct linguistic processes.